PENGGUNAAN F-CHARTA DAN PRAKTIK DENGAN BAHAN SEDERHANA UNTUK MENINGKATKAN MINAT PESERTA DIDIK DALAM PEMBELAJARAN IPA-FISIKA PADA MATERI POKOK LISTRIK STATIS - Sunardi, Sunardi (Vidya Karya Jurnal Kependidikan, 2013)
Natural Science is a science that deals with how to find out about the nature systematically and not just a collection of knowledge of facts, concepts, or principles only. So, science learning must be carried out with three components of scientific works, those are scientific process, scientific attitude and scientific products. Classroom action research aims to improve student interest in science-physics learning in the topic Electrostatic using instructional media F-Charta and practice with simple materials. The subjects of research are teacher of Science Physics SMP Negeri 1 Banjarmasin (as researchers) and students of class IX E of SMP Negeri 1 Banjarmasin, academic year 2013-2014. The object of research is students interest in science-physics learning of electric static. The research consist of two cycles, each cycle consisting of two learning activities section. The result of research showed an increase in student interest, which 21.74% of attitude increase and 22.72% responsiveness increase from the first cycle to the second cycle. Based on the results of this research concluded that physics science learning of electrostatics using instructional media F-Charta and practice with simple materials can increase student interest in learning of IX E SMP Negeri 1 Banjarmasin in the 1st half of the academic year 2013-2014.